Peran Mata Kuliah Islam dan Budaya Jawa dalam Menghadapi Ujaran Kebencian - Eko Nur Wibowo (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
AbstractThe times by increasing the sophistication of science and technology have led to an increase in the flow of communication in Indonesia. Increasing the flow of cyberspace communication is increasingly widespread with various forms of communication both leading to positive and negative things such as hate speech. If negative forms of communication such as hate speech are not immediately prevented or overcome, it can have a negative impact on the unity and integrity of the Indonesian state. Therefore there is a need for treatment, one of the forms of handling is by optimizing tertiary institutions through the three principles of Tri Darma, education, research and service. In this case the author, examines the role of Islamic subjects and Javanese culture in dealing with expressions of hatred. The aim is to find out the role of Islamic tertiary institutions in preventing or overcoming hate speech, more specifically through these courses. The research method used in this paper is a qualitative analytical descriptive method. This course teaches a number of attitudes and principles of life that are relevant to Islamic teachings and are compatible with the principles of peace including universal attitudes, tolerance, understanding of togetherness and diversity, ngajeni marang liyan (respecting others). So this subject needs to be optimized in preventing or overcoming the utterance of hatredKeywords: Islam and Javanese Culture, hate speech.